Right-wing extremism and the well-being of immigrants - Andreas Knabe; Steffen Rätzel; Stephan L. Thomsen (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2009)
This study analyzes the effects of right-wing extremism on the well-being of immigrants based on data from the German Socio-Economic Panel (SOEP) for the years 1984 to 2006 merged with state-level information on election outcomes. The results show that the life satisfaction of immigrants is significantly reduced if right-wing extremism in the native population increases. Moreover ; the life satisfaction of highly educated immigrants is affected more strongly than that of low-skilled immigrants. This supports the view that policies aimed at making immigration more attractive to the high-skilled have to include measures that reduce xenophobic attitudes in the native population.
Keywords: I31; R23; J15; 300; Well-Being; Life Satisfaction; Right-Wing Extremism; Migration; SOEP; Migranten; Hochqualifizierte Arbeitskräfte; Lebenszufriedenheit; Ethnische Diskriminierung; Deutschland